2002
DOI: 10.1016/s0014-5793(02)02695-9
|View full text |Cite
|
Sign up to set email alerts
|

PspE (phage‐shock protein E) of Escherichia coli is a rhodanese

Abstract: The psp (phage-shock protein) operon of Escherichia coli is induced when the bacteria are infected by filamentous phage and under several other stress conditions. The physiological role of the individual Psp proteins is still not known. We demonstrate here that the last gene of the operon, pspE, encodes a thiosulfate:cyanide sulfurtransferase (EC 2.8.1.1; rhodanese). Kinetic analysis revealed that catalysis occurs via a double displacement mechanism as described for other rhodaneses. The K m s for SSO 23 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…Nevertheless, a picture is starting to emerge of an enzyme activity that is up-regulated in response to stress. Rhodanese and proteins containing rhodanese-like domains are implicated in response to heat shock, phage shock, and senescence (13,23). MSTs have been implicated in the management of oxidative stress (27,28), and the trypanosomatid LmMST is also linked to cysteine biosynthesis (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a picture is starting to emerge of an enzyme activity that is up-regulated in response to stress. Rhodanese and proteins containing rhodanese-like domains are implicated in response to heat shock, phage shock, and senescence (13,23). MSTs have been implicated in the management of oxidative stress (27,28), and the trypanosomatid LmMST is also linked to cysteine biosynthesis (27).…”
Section: Resultsmentioning
confidence: 99%
“…For example, sulfurtransferases may be involved in the formation and maintenance of iron-sulfur clusters in protein (4,5), detoxification of cyanide (6,7), degradation of cysteine (8), biosynthesis of the molybdopterin cofactor of xanthine oxidase (9), selenium metabolism (2,10), and thiamine and 4-thiouridine biosynthesis (11,12). The expression of specific sulfurtransferases is up-regulated under conditions of peroxide or hypo-sulfur stress, osmotic shock, and phage infection (13), suggesting that such enzyme activity is protective of the cell and/or involved in repair processes. Nevertheless, despite intensive study, the biological functions and identification of the physiological substrates of sulfurtransferases remain uncertain.…”
mentioning
confidence: 99%
“…Interestingly, structural and functional studies performed on the E. coli TST GlpE, containing a single 108-amino acid rhodanese domain, demonstrated that a single domain can be selfsufficient for thiocyanate formation from thiosulfate in the presence of cyanide (15) Single catalytic rhodanese domain proteins are encoded by both eukaryotic and prokaryotic genomes. These proteins have been associated with specific stress conditions as in the case of the Drosophyla melanogaster heat shock protein 67-B2, of the E. coli phage-shock protein E (PspE) (16), and of the Vibrio cholerae shock protein Q9KN65 (17). Proteins containing single rhodanese domain have also been associated with the process of leaf senescence in plants.…”
Section: Group I: Single Domain Proteinsmentioning
confidence: 99%
“…The rhodanese homology domain has a conserved cysteine residue that participates in catalysis (12). The ϳ110-amino acid rhodanese domain may comprise the entire protein, as in the GlpE and PspE rhodaneses of E. coli (13,14), or the domain may be fused to other protein domains of known or unknown function. Other rhodaneses and mercaptopyruvate sulfurtransferases contain two rhodanese homology domains, but only the C-terminal domain contains an active site cysteine that participates in catalysis (12).…”
mentioning
confidence: 99%